Sustainable Food System Assessment Lessons from Global Practice - Blay-Palmer, Alison; Conaré, Damien; Meter, Ken; Di Battista, Amanda; Johnston, Carla (Routledge Studies in Food, Society and the Environment, 2019)
food supply; environmental aspects; sustainable agriculture; nutrition policy